Simultaneous Estimation of Menaquinone-7 and Cholecalciferol in Combined Pharmaceutical Dosage Forms by Ultraviolet Spectrophotometry - Verma, Hitesh (Asian Journal of Pharmaceutics (AJP), 2019)
Context: Simple, precise, easy, and accurate spectrophotometric methods are ideal for regular quality control purpose. Menaquinone – 7 (MK-7) and cholecalciferol (CHOL) are two vitamins which work in synergy to elicit pharmacological responses in body. Inspite of multiple available brands of these two vitamins in market, to the best of our knowledge, there is no spectrophotometric method available for simultaneous quantification of these two vitamins. Therefore, an attempt was made in present research to develop two simple, precise, rapid, accurate, and economical spectrophotometric methods for simultaneous estimation of MK-7 and CHOL in combined pharmaceutical dosage forms. Materials and Methods: Method I was based on dual-wavelength method while Method II was based on Q-absorbance ratio method. Validation of developed methods was done as per the International Conference on Harmonization guidelines, and developed methods were applied for the determination of MK-7 and CHOL in laboratory prepared admixtures as well as in-house formulated dosage form. Results: Beer’s law was obeyed over concentration range of 5–35 μg/mL for both MK-7 and CHOL (values of correlation coefficient were close to 1). Developed methods are accurate, reproducible, precise, and robust for determination of these two vitamins (percent recoveries lies within range of 98–102% while associated relative standard deviation was <2%). Conclusion: Developed methods can be used for quantification of MK-7 and CHOL in pharmaceutical dosage forms during regular quality control analysis.